2022
DOI: 10.3390/children9081203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Participating in Martial Arts in Children: A Systematic Review

Abstract: Background: The application of various martial arts programs can greatly contribute to improving the of physical fitness of preschool and school children. The purpose of this review paper was to determine the effects and influence that martial arts program intervention has on children’s physical fitness, which includes motor skills and the aerobic and anaerobic abilities of children. Method: We searched the following electronic scientific databases for articles published in English from January 2006 to April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Despite the lack of a significant relationship, in most of the traits compared in each of the four groups divided by age and gender, it was observed that in at least 3 of the 5 tests, the participants who were martial art practitioners obtained higher results compared to the control group. The results of a number of studies conducted by researchers show the positive impact of participation in sports by people of different ages on their fitness levels relative to physically inactive peers [10,24,38]. Depending on their expertise, taekwondo athletes have different levels of motor aptitudes.…”
Section: Discusionmentioning
confidence: 99%
“…Despite the lack of a significant relationship, in most of the traits compared in each of the four groups divided by age and gender, it was observed that in at least 3 of the 5 tests, the participants who were martial art practitioners obtained higher results compared to the control group. The results of a number of studies conducted by researchers show the positive impact of participation in sports by people of different ages on their fitness levels relative to physically inactive peers [10,24,38]. Depending on their expertise, taekwondo athletes have different levels of motor aptitudes.…”
Section: Discusionmentioning
confidence: 99%
“…As the movement exploded, there was an awareness that martial arts had fitness benefits [9,10], spurring participants who would never likely fight but would participate in training for the perceived benefits. The physiological, neurological, emotional, and cognitive results of training are also factors that lead to improved performance [11][12][13][14]. Martial arts is a synergy of body, mind, and spirit, so the challenge for martial artists is a four-prong test: physical, mental, emotional, and spiritual.…”
Section: The Fitness Extension Of Martial Arts: Performance and Trainingmentioning
confidence: 99%
“…Therefore, it seems justified to perform additional research with the participation of athletes of combat sports such as WKF karate, which is frequently recommended as a physical activity that is a golden mean for correction of postural disturbances and improvement of postural control [9,18,19]. Therefore, the aim of this study was (1) to assess the acute (after kata training) and long-term (years of kata training) effects of kata training on body posture (spinal curvatures, pelvic tilt) and ROM, and (2) to evaluate the prevalence and location of musculoskeletal pain in elite karate athletes. It was hypothesized that kata training induces acute changes in the depth of the anteroposterior spinal curvatures, pelvic tilt, and ROM.…”
Section: Introductionmentioning
confidence: 99%
“…Among different forms of physical activity, martial arts are known to be a universal sport that stimulates all three groups of motor abilities in preschool and school children [ 1 ], i.e., (i) strength and conditioning abilities (strength, endurance), (ii) complex abilities (speed, agility), and (iii) coordination abilities [ 2 ]. It also impacts positively on socio-psychological responses and mental health [ 1 ]. Even though many combat sports can be listed under the term ‘martial arts’, karate is considered to be one of the most popular combat activities worldwide, both in children and adults [ 3 ].…”
Section: Introductionmentioning
confidence: 99%